PKM Desain dan Konsultasi Rumah Sehat di Desa Mekarwangi, Banten - Muhammar Khamdevi; Andrey Caesar Effendi; Danang Harito Wibowo (Prodi Arsitektur Universitas Matana, 2020)
The houses in Kampung Cilegong, Mekarwangi Village are still far from the standard of Healthy Homes. Although some were built by artisans with the knowledge of